Relationship between dental plaque formation and salivary cortisol level in pregnant women - Mehdi Shri̇nzad; Reza Omrani̇; Ali Rıza Soltani̇an; Ali Ghalei̇ha; Parviz Torkzaban; Safoura Taheri̇; Azita Ti̇znobai̇k (European Oral Research, 2019)
Purpose Understanding how increased level of salivary cortisol contributes to the development of dental biofilm during pregnancy can help inthe prevention of dental caries and periodontal diseases. This study aims to evaluate the relationship between salivary cortisol level and dental biofilm formation in pregnant women. Patients and Methods This descriptive-analytic study was conducted in Hamadan, Iran in 2011. Forty consecutive pregnant women with no history of abortion, stillbirth, or any known physical or psychological disorders at weeks 25 and 33 of gestation were included. Salivary samples were collected for measurement of cortisol levels by Enzyme Linked Immunoabsorbent Assay (ELISA) method. The amount and extension of dental biofilms were determined by using a disclosing agent. Data were analyzed using descriptive and analytical statistics in SPSS version 16. Results The mean levels of salivary cortisol at weeks 25 and 33 of gestation were respectively, 2.45 ± 1.56 µg/dl and 5.24 ± 4.07 µg/dl which demonstrates a significant difference (P<0.001). Evaluation of dental biofilm at two time intervals revealed a significant increase in amount of dental biofilm at week 33 of gestational period (34.65 ± 10.9% vs. 42.45 ± 12.35%, P<0.001). Elevated levels of dental biofilm were significantly correlated with salivary cortisol levels at week 33 (r=0.494, P=0.001),however, it was not significant at week 25 of gestation (r=0.148, P=0.361). Conclusion The findings suggested that increased levels of salivary cortisol can predict dental biofilm formation and accumulation in pregnant women in the last weeks of gestation.